If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2k=k-6/2
We move all terms to the left:
2k-(k-6/2)=0
We add all the numbers together, and all the variables
2k-(k-3)=0
We get rid of parentheses
2k-k+3=0
We add all the numbers together, and all the variables
k+3=0
We move all terms containing k to the left, all other terms to the right
k=-3
| 34=4w-10 | | 8(x+9=88 | | 3x²-20x+12=0 | | 50=5(x=+50 | | |3x+12|=26 | | (3)(2^x)=(2)(5^x) | | x-(x*0,25)=1500 | | -75x+24=-26 | | 2.7x3.8=10.26 | | X=5y+9/6 | | 3x+4=-7x-24 | | 6x+19=10x-9 | | 6x-+19=10x-9 | | 2x+14=-x+32 | | 10x+4=5x+34 | | 10x+9=3x-40 | | (x÷2-x÷5)=12 | | A+B=(AxB)+A | | 2(3x+4)+3(x+5)=50 | | x÷2-x÷5=12 | | 5x-6=2x-26 | | 7×(2x-1)=35 | | 6x+8+3x+15=50 | | 3×(5x+2)=21 | | 9x9=19 | | x2-7=42 | | (3x+6)÷5=-6 | | 4(3x+2)=5(2x-6) | | 1-6a=2a7 | | -2t+10=2t−2 | | 4g=2g+10 | | -10p=-9p−3 |